Association Between Disability and Life Satisfaction, Participation, and Psychological Health: A Traumatic Brain Injury Model Systems Study - Golden, Katherine; Ketchum, Jessica M; Talley, Kelli G; Rabinowitz, Amanda; Juengst, Shannon; Dams-O'Connor, Kristen; Weaver, Jennifer A; O'Neil-Pirozzi, Therese M; Giacino, Joseph T; Bodien, Yelena G (Neurology, 2025)
Moderate-to-severe traumatic brain injury (TBI) can result in disability across physical, social, and cognitive domains. The Glasgow Outcome Scale-Extended (GOSE), which evaluates global function, is the most frequently used TBI outcome measure. However, the GOSE may not capture all domains of recovery. We evaluated the relationship between the GOSE and domain-specific measures of life satisfaction, participation, and psychological health 1 year after TBI. We analyzed prospectively collected data from participants of the TBI Model Systems (TBIMS) study enrolled between 2010 and 2022 who completed the GOSE and at least 1 additional outcome measure 1 year after injury. We conducted pairwise comparisons to determine whether adjacent GOSE categories (e.g., GOSE 3 vs 4) are associated with different Satisfaction With Life Scale (SWLS), Participation Assessment of Recombined Tools-Objective (PART-O), Patient Health Questionnaire-9 (PHQ-9), and Generalized Anxiety Disorder-7 (GAD-7) scores. We report median differences (MDs) with 95% CIs. We also dichotomized each measure and calculated the proportion of participants above and below cut points associated with "favorable" compared with "unfavorable" GOSE outcomes. Among 19,245 participants enrolled in the TBIMS study, 7,568 participants (median [interquartile range] age 44 [27-61] years, 73% [5,541/7,568] male, 27% [2,020/7,568] female, 66% [5,007/7,568] White) met inclusion criteria. After correcting for multiple comparisons, there were no differences in median scores on SWLS between GOSE 3 vs 4 (MD = -1.00 [CI -1.00, 0.00]; = 0.21) and GOSE 4 vs 5 (0.00 [-1.00, 1.00]; = 0.5); PART-O between GOSE 7 vs 8 (-0.10 [-0.13, -0.06]; = 0.0084); PHQ-9 between GOSE 3 vs 4 (0.00 [-1.00, 1.00]; = 0.91) and GOSE 4 vs 5 (0.00 [0.00, 1.00]; = 0.42); and GAD-7 between GOSE 3 vs 4 (0.00 [0.00, 0.10]; = 0.07), GOSE 4 vs 5 (0.00 [0.00, 0.00]; = 0.66), and GOSE 5 vs 6 (0.00 [0.00, 0.00]; = 0.40). Among those with an "unfavorable" outcome (GOSE score ≤4), 44% (601/1,371), 8% (191/2,491), 67% (536/803), and 75% (602/807) had scores in the normative range for SWLS, PART-O, PHQ-9, and GAD-7, respectively. Overreliance on functional outcome measures such as the GOSE in postacute TBI assessment fails to capture critically important aspects of recovery that fall outside this domain. Persons with more functional disability often report similar levels of life satisfaction, participation, and psychological health as those with less disability. Clinicians should recognize that bidirectional dissociations between level of disability and ratings of well-being are common and should be evaluated accordingly.